Comparing TomoHelical and TomoDirect in postmastectomy hypofractionated radiotherapy after immediate breast reconstruction. (October 2021) - Dicuonzo, Samantha; Patti, Filippo; Luraschi, Rosa; Frassoni, Samuele; Rojas, Damaris Patricia; Zaffaroni, Mattia; Morra, Anna; Gerardi, Marianna Alessandra; Zerella, Maria Alessia; Emiro, Francesca; Cattani, Federica; Bagnardi, Vincenzo; et al.
Highlights: Aim of the study is to compare TD and TH plans in HF PMRT setting for selected pts. TD plans were re-planned on TH with same prescription dose and constraints. TD compared to TH reached a good target coverage, with an optimal sparing of OARs. Abstract: Background: Postmastectomy radiotherapy (PMRT) with TomoHelical™ (TH) or TomoDirect™ (TD) allows a uniform target coverage. In this study, we compare treatment plans using TD and TH in the setting of hypofractionated PMRT and immediate breast reconstruction. Material and methods: The TD-treatment plans of breast cancer patients treated between May 2016 and August 2019 were retrospectively selected. All the TD plans were re-planned on TH with the same prescription dose (40.05 Gy/15 fractions) and according to our dose/volume constraints. Data about the 2 treatment plans were compared with a focus on PTV coverage and all the organs at risk (OARs) constraints. Results: Fifty patients for a total number of 100 treatment plans (50 with TD and 50 re-planned with TH) were analyzed. All the median value in the TD PTV CHEST WALL plans fulfilled the predefined planning objectives, even though TH emerged as best for target coverage with statistically significant difference for V90%. TD provided the lowest V95% for the PTV SVC, but the median value was near to the recommended value of 90% (89.8 % vs 98.6% for TD and TH, respectively). Overall, TD reached the best OARs sparing. The main statistically significant differences with TH were for contralateral breast, ipsilateral and contralateral lung. All the other dose values for TH were higher than TD, but they fulfilled the recommended/acceptable predefined planning objectives. Conclusions: In the setting of PMRT, TD compared to TH reached an acceptable target volume coverage, with an optimal sparing of OARs.